Dietary gangliosides rescue GM3 synthase deficiency outcomes in mice accompanied by neurogenesis in the hippocampus - Inokuchi, Jin-ichi; Go, Shinji; Suzuki, Akemi; Nakagawasai, Osamu; Odaira-Satoh, Takayo; Veillon, Lucas; Nitta, Takahiro; McJarrow, Paul; Kanoh, Hirotaka; Inamori, Kei-ichiro; Tan-No, Koichi; Collett, Michael (Frontiers in Neuroscience, 2024)
Ganglioside GM3 synthase is a key enzyme involved in the biosynthesis of gangliosides.GM3 synthase deficiency (GM3SD) causes an absence of GM3 and all downstream biosynthetic derivatives including all the a/b/c series gangliosides commonly found in neural tissues. The affected individuals manifest with severe irritability, intractable seizures, hearing loss, blindness, and profound intellectual disability. It has been reported that some significant improvements in clinical symptoms, growth parameters, and developmental and cognitive scores in GM3SD patients have been achieved through oral ganglioside supplementation. To gain insight into the molecular mechanisms of this supplementation, we performed oral bovine milk gangliosides supplementation to GM3 synthase deficient mice from early weaning periods. The oral milk ganglioside preparations were dominated by GM3 and GD3 gangliosides. Oral milk ganglioside supplementation showed improvement of the decreased cognitive function symptom seen in GM3 synthase deficient mice. The improvement in cognitive function was accompanied with increased ganglioside levels and neurogenesis in the hippocampus in the supplemented animals.